The relationship between nutritional status and acute upper respiratory infection among young children in Metro Cebu, Philippines / Nguyen Dang Vung - Nguyen Dang Vung
The effect of nutritional status on acute upper respiratory infection (AURI) morbidity in children from four months to two years of age examined by using data from a 1983-1986 Cebu longitudinal health and nutrition study (CLHNS) of 3,080 non-twin live births among a sample of mother-infant pairs. In bimonthly intervals (i.E., every two months), for a period of two years, detailed information were collected on health, symptoms of AURI, diarrhea, anthropometry of both mothers and infants and related demographic and socioeconomic variables. The prevalence of AURI at the time of interview and during a 7-day period prior to the interview was linked to the anthropometric data at each measuring point. EPI INFO for descriptive and stratified analysis; GLIM, SPSS softwares for multiple logistic regression were used to study the association between nutritional status and AURI. Undernutrition measured by a) Stunting (height-for-age Z-score less than - 2 SD using the National Centre for Health Statistics (NCHS) median reference population and b) wasting (weight-for-height Z-score less than - 2 SD using the NCHS median reference population) and c) combined stunting and wasting, was significantly associated with morbidity of AURI with the following Mantel-Haenszel Weighted Odds Ratios: 1.12 (95CI: 1.05, 1.19); 1.48 (95CI: 1.26, 1.74) and 1.66 (95CI: 1.42, 1.94), respectively.By conducting multiple logistic regression separately for 11 survey rounds using height-for-age Z-score and weight-for-height Z-score as continuous variables, and later summarized by Meta-analysis, it was found that undernutrition as measured by height-for-age Z-score and weight-for-height Z-score, was significantly indirectly associated with AURI with the following pooled Odds Ratios: 0.9287 (95CI: 0.9277, 0.9298) and 0.8232 (95CI: 0.8219, 0.4245), respectively. This means that for each unit increase in height-for-age, the probability of getting AURI decreased by 0.93 and 0.82, respectively. These Odds Ratios remained significant when adjusted for potential confounding effects of breast-feeding, season, cooking fuel, household income and assets, low birth weight, sex of children and vitamin supplementation.At the end of 24 months, summary multiple logistic regression model, using as dependent variable the number of times AURI occurred in 11 survey rounds and as independent variables the number of times the child was stunted; or the number of times the child was wasted, or the number of times the child was both wasted and stunted through 11 survey rounds, while adjusting for potential confounding variables such as sex of the child; number of times the child was interviewed in rainy/dry season; breast-feeding status; low birth weight, household income and assets, immunization status and vitamin supplementation, stunting and wasting were found to be significantly associated with morbidity of AURI.By conducting longitudinal analysis (Markov model, first order), wasting and combination of wasting and stunting were both found to be significantly associated with the prevalence of AURI.In general, undernutrition as measured by stunting, wasting, and the combination of wasting and stunting, by height-for-age Z-score or weight-for-height Z-score, was significantly associated with prevalene of AURI. This study provides further evidence that undernutrition is a major determinant of AURI morbidity among young children.